2002
DOI: 10.1038/sj.bjc.6600169
|View full text |Cite
|
Sign up to set email alerts
|

Isolated limb perfusion with actinomycin D and TNF-alpha results in improved tumour response in soft-tissue sarcoma-bearing rats but is accompanied by severe local toxicity

Abstract: Previously we demonstrated that addition of Tumour Necrosis Factor-a to melphalan or doxorubicin in a so-called isolated limb perfusion results in synergistic antitumour responses of sarcomas in both animal models and patients. Yet, 20 to 30% of the treated tumours do not respond. Therefore agents that synergise with tumour necrosis factor alpha must be investigated. Actinomycin D is used in combination with melphalan in isolated limb perfusion in the treatment of patients with melanoma in-transit metastases a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
1
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 22 publications
0
3
1
1
Order By: Relevance
“…At this regard, several studies showed an association between elevated circulating TNF- α levels and cancer development [ 120 , 121 ] stimulating cell proliferation [ 122 ], causing DNA damage [ 123 ] and promoting angiogenesis [ 124 ]. This data was not confirmed by other studies that reported a direct cytotoxic effect of TNF- α on tumoral cell [ 125 ], an indirect action on tumor vessels [ 126 ] and a synergic action with conventional antineoplastic agents [ 127 , 128 ].…”
Section: Resultscontrasting
confidence: 83%
“…At this regard, several studies showed an association between elevated circulating TNF- α levels and cancer development [ 120 , 121 ] stimulating cell proliferation [ 122 ], causing DNA damage [ 123 ] and promoting angiogenesis [ 124 ]. This data was not confirmed by other studies that reported a direct cytotoxic effect of TNF- α on tumoral cell [ 125 ], an indirect action on tumor vessels [ 126 ] and a synergic action with conventional antineoplastic agents [ 127 , 128 ].…”
Section: Resultscontrasting
confidence: 83%
“…However, TNF-␣ alone shows only marginal activity, even with administration at high doses through local drug delivery systems. To increase ma- lignant cell sensitivity to TNF-␣, it is combined with conventional antineoplastic agents (e.g., melphalan, paclitaxel, and actinomycin D) in clinical use (Manusama et al, 1996;de Wilt et al, 2000;Seynhaeve et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…24,27,28 Antitumor effects of TNF are enhanced by a combination of this cytokine with several classic chemotherapeutics. [29][30][31] Proteasome inhibition prevents NFjB activation, therefore, enhancing proapoptotic effects of TNF in many but not all cancer cell types. [32][33][34] Moreover, proteasome inhibition may alleviate the inflammatory response elicited by TNF.…”
mentioning
confidence: 99%